EFFECT OF NANOMATERIALS IN CEMENT MORTAR CHARACTERISTICS - WAIL N. AL-RIFAIE; WALEED K. AHMED (Journal of Engineering Science and Technology, 2016)
Concrete is considered as brittle materials and widely used due to high compressive strength but unfortunately having and has low tensile strength that has a numerous negative impacts on the lifespan of concrete made structures. Therefore, mechanical properties of cement mortar have been investigated experimentally using different types and ratios of nano material to improve the properties. Since the strength of the concrete is of high importance, different materials have been used to enhance the compressive and the tensile characteristics of the cement mortar compressive and tensile strength. Mainly, this objective has been implemented through using micro cement, micro sand, nano silica, and nano clay in developing a nano-cement mortar which can to improve the concrete for the constructional applications. The samples were prepared and tested under tensile and compressive mode according to ASTM-2011 regulations for concrete. The parameters that are taken consideration during the investigation were micro sand, micro cement, nano silica, developed nano clay, and naphthalene sulphonate as super- plasticizers. In general, it has been observed that the results showed a significant increase in both compressive and tensile strength of the mortar at early stages of hardening, where a maximum increase of 22% in the compressive strength was achieved , whereas 3.7 time increase in the compressive strength was recorded over the tradition levels of the concrete strength.